Does gestation or feeding affect the body temperature of the golden lancehead, Bothrops insularis (Squamata: Viperidae) under field conditions? - Bovo, Rafael P. [UNESP]; Marques, Otavio A. V.; Andrade, Denis V. [UNESP] (Sociedade Brasileira de Zoologia, 2010)
Temperature affects physiological performance in reptiles and, therefore, body temperature (Tb) control is argued to have an important adaptive value. Alterations in Tb due to transient changes in physiological state, as during digestion or gestation, are often linked to the potential benefits of a more precise Tb regulation. However, such thermoregulatory responses in nature remain controversial, particularly for tropical snakes. Herein, we measured Tb of the golden lanceheads, Bothrops insularis (Amaral, 1921), at Queimada Grande Island, southeastern Brazil, to test for alteration in selected body temperatures associated with feeding or gestation. We found no evidence that postprandial or gravid snakes selected for higher Tb indicating that, under natural conditions, body temperature regulation in B. insularis apparently encompasses other ecological factors beyond physiological state per se.
Keywords: Digestion; gravid females; postprandial thermophilic response; snake; thermoregulation; Neotropics